Profiling antinutritional and antioxidant activities of bitter leaf (vernoniaamygdalina) flower - Odokwo, Edet Okon; Eze, Precious (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
The antinutritional and antioxidant profiling of the floral parts of the bitter leaf was carried out. The collected floral parts of the bitter leaf were air-dried, pulverized and macerated using absolute ethanol. The concentrated form of the extract (EEF) was subjected to both qualitative and quantitative anti-nutritional profiling using standard procedures. The anti-oxidant profiling of EEF was established using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric ion-reducing antioxidant potential (FRAP) methods. The result of the qualitative analysis indicated the presence of alkaloids, flavonoids, phenols, steroids (terpenoids), quinones, coumarins, anthocyanins, tannins and saponins while quantitatively, alkaloids (1.56±0.02 mg of atropine equivalent, AE), flavonoids (25.278±0.555 mg of quercetin equivalent, QE), total phenolics (14.457±0.231 mg of gallic acid equivalent, GAE), tannins (5.585±0.026 mg of GAE) and saponins (1.27±0.03) % in the floral part of bitter leaf. The antioxidant activity of EEF increases as its concentration increases with a corresponding increase in concentration from 25 μg/ml to 400 μg/ml. The ferric ion reducing potential of EEF was observed at 400 μg to have 198.257±0.002 mg ascorbic acid, AAE. The floral part of the bitter leaf is rich in anti-nutrients and anti-oxidant activity.